THE CURRENT SITUATION OF MEDICAL STAFF COMMUNICATION WITH PATIENTS IN HOC MON STATE REGISTRATION HOSPITAL (Vietnam Journal of Community Medicine, 2020)
Background: In addition to the professional capacity and ethical qualities, the attitude and communication behavior of medical staff with patient are important prefix can not missing, in order to create trust, satisfy patients and create quality medical examination and treatment services. Objective: Determine the state of behavioral communication and a number of factors related to the actual state of medical staff communication with patients at Hoc Mon State Registration Hospital in 2020. Methods: Cross-sectional descriptive. Results: Assessment of the importance level of communication skills in medical staff communication with the patient is 85.2% or more. In which, the level of importance: skills to establish relationships when communicating with patients 85%, listening skills to patients 91.1%; expression skills 94%, questioning skills 87.3%; emotional and behavior control skills 90.5%. Over 90% of research subjects agree with the benefits and importance of medical staff communication skills with patients during medical examination and treatment. The department’s characteristics are related to the assessment of the importance of communication with patients during medical examination and treatment. Income is positively correlated with assessment of the importance of communication with patients during medical examination and treatment. Conclusions: The actual state of medical staff communication with patients at Hoc Mon General Hospital is relatively good in both aspects: awareness and communication practice.
Keywords: Communication, behavior, medical staff, Likert, Hoc Mon registered hospital